It's all about Him : finding the love of my life - Jackson, Denise J., 1960-; Vaughn, Ellen Santilli (Nashville, Tenn. : Thomas Nelson, 2007)
This inspirational book gives the reader an intimate look into one of country music's most famous couples: their love story, struggles, dreams, success, the near-failure of their marriage, and the rediscovery of their faith and how that has reshaped their lives. Provided by the publisher.
A Cinderella story? -- Little bitty beginnings -- Where he came from -- Shock -- Surprises -- High hopes -- Daunting disappointments -- Dreams come true -- Life throws curves -- Spotlights and shadows -- Delights and distractions -- Turning my eyes -- When dreams die -- Letting go -- Praying new prayers -- Taking small steps -- Coming home - - A hard road -- Making new vows -- A work in progress -- What really matters -- Roots -- Precious memories -- Drive! -- Happily ever after, even when we're not.
Includes bibliographical references (p. 233-236).
Keywords: Jackson, Alan, -- 1958- -- Marriage; Jackson, Denise J., -- 1960- -- Marriage; Country musicians' spouses -- United States -- Biography; Country musicians -- United States -- Biography; Christian biography -- United States